Typen aus der Sammlung G. A. Lohse (1910-1994), Hamburg, im Deutschen Entomologischen Institut (Coleoptera: Hydrophilidae, Cholevidae, Melyridae, Elateridae, Cucujidae, Cryptophagidae, Lathridiidae, Mycetophagidae, Cisidae, Anobiidae, Chrysomelidae). - Zerche, Lothar (Contributions to Entomology = Beiträge zur Entomologie, 1996)
The types of the G. A. Lohse collection (Coleoptera excluding Staphylinidae), which were donated to the Deutsches Entomologisches Institut, are listed. They comprise 47 specimens of 23 species and subspecies, among them 16 holotypes.